Narrative beginnings : theories and practices - Richardson, Brian, 1953- (Frontiers of narrative., 2008)
George Eliot wrote that "man cannot do without the make-believe of a beginning." Beginnings, it turns out, can be quite unusual, complex, and deceptive. The first major volume to focus on this critical but neglected topic, this collection brings together theoretical studies and critical analyses of beginnings in a wide range of narrative works spanning several centuries and genres. The international and interdisciplinary scope of these essays, representing every major theoretical perspective--including feminist, cognitive, postcolonial, postmodern, rhetorical, ethnic, narratological, and hypert